2016
DOI: 10.5897/ajpp2016.4551
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anthelmintic activity of Allium sativum, Allium cepa and Jatropha curcas against Toxocara canis and Ancylostoma caninum

Abstract: Prevalence of animal diseases is one of the major livestock production constraints in Kenya with high impacts on livelihoods due to related economic losses affecting food security in the country. The use of synthetic drugs for disease management has challenges. This makes the use of medicinal plants for treatment a rational alternative. Ascarids, Toxocara canis and Ancylostoma caninum are among the most frequently observed helminth parasites in dogs in Kenya. The two parasites are also known to cause helminthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 5 publications
1
19
0
1
Order By: Relevance
“…The result of the phytochemical screening showed that the extract of Allium cepa and Allium sativum contain, flavonoid, alkaloid, glycosides, saponin, tannin (Table 4). This is in agreement with the work done by Orengo et al [27]. The phytochemical components present are known to possess both physiological and as well as medicinal activities.…”
Section: Resultssupporting
confidence: 93%
“…The result of the phytochemical screening showed that the extract of Allium cepa and Allium sativum contain, flavonoid, alkaloid, glycosides, saponin, tannin (Table 4). This is in agreement with the work done by Orengo et al [27]. The phytochemical components present are known to possess both physiological and as well as medicinal activities.…”
Section: Resultssupporting
confidence: 93%
“…Consistent with this finding, Verocai et al (2010) observed that T. canis eggs exposed to sodium hypochlorite were morphologically damaged, but still formed larvae and remained infective for 2 weeks. Additionally, ethanol extracts of Allium cepa and Allium sativum showed good anthelmintic activity against T. canis since they affected the survival of larvae (Orengo et al 2016). Also, Z. officinale ethanol extract at the concentration of 800 lg/mL induced programmed death in Trichomonas vaginalis in vitro (Arbabi et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To aid visualisation of the results, these raw values have been reported using line graphs created by the author of this Knowledge Summary. (day [11][12] The author of this Knowledge Summary also undertook the following analysis on the data reported in the original paper:…”
Section: Main Findings: (Relevant To Pico Question)mentioning
confidence: 99%
“…Palacious-Landin et al, 2015; Orengo et al, 2016; Tavassoli et al, 2018) efficacy (differing stages of the life cycle, dependent on the study) against various species of helminth. This includes in vitro activity against some species (Toxocara canis, Ancylostoma caninum) that infest dogs(Orengo et al, 2016). Consequently, scientific and veterinary growth in its interest in a wormer for dogs and cats may be likely to develop over time.…”
mentioning
confidence: 99%